Geophilus arenarius, a long-misunderstood species in the still unresolved carpophagus species-complex (Chilopoda: Geophilidae) - Bonato, Lucio; Minelli, Alessandro (Zootaxa, 2011)
Geophilus arenarius Meinert (Chilopoda: Geophilidae), a neglected nominal species from north-western Africa of uncertain identity, is here described in detail and its taxonomic position assessed. G. arenarius is actually a morphologically distinct species belonging to a widespread Western Palaearctic species-complex whose internal taxonomy is still largely unresolved, to the exclusion of the two British species G. carpophagus and G. easoni. G. arenarius differs from both other species mainly by lacking a transverse suture on the head, lacking peculiar integumental features (carpophagus-structures) along the trunk, and having relatively stouter antennae and forcipular coxosternite.